(E)-1-[4-(Hexyloxy)phenyl]-3-(2-hydroxyphenyl) prop-2-en-1-one - Siti Muhaini, Haris Fadzillah; Zainab, Ngaini; Hasnain, Hussain; Ibrahim, Abdul Razak; Safra Izuani, Jama Asik (US National Library of Medicine National Institutes of Health, 2012)
In the title compound, C21H24O3, the enone moiety adopts an s-cis conformation and the dihedral angle between the benzene rings is 12.89 (6). The hexyloxy tail adopts an extended conformation. In the crystal, inversion dimers are linked by pairs of O—H O hydrogen bonds and pairs of C— H O interactions, forming two R2 2(7) and one R2 2(10) loops. The dimers are then arranged into sheets lying parallel to (201) and weak C—H interactions consolidate the packing.